2023
DOI: 10.1039/d2sm01642g
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the balance between additives’ miscibility and plasticisation effect in polymer composites: a computational study

Abstract: Plasticisers are small organic molecules routinely added to polymer composites that modify the processability of the compounds by adsorbing on the filler’s surface or dispersing into the polymer matrix. Here...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…and N PL and N PI are the numbers of PL and PI beads, respectively. We elected to only study one PI chain length based on our previous work using the same model, 33 in which PI lengths of 1, 10, 150, and 300 were investigated. It was found that, for each PL molecule studied, the miscibility was consistent regardless of PI length, with the exception of the PI solvent (i.e., a monomer solution), for which all PLs studied were miscible.…”
Section: ■ Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…and N PL and N PI are the numbers of PL and PI beads, respectively. We elected to only study one PI chain length based on our previous work using the same model, 33 in which PI lengths of 1, 10, 150, and 300 were investigated. It was found that, for each PL molecule studied, the miscibility was consistent regardless of PI length, with the exception of the PI solvent (i.e., a monomer solution), for which all PLs studied were miscible.…”
Section: ■ Methodologymentioning
confidence: 99%
“…We further simulated rigid, rod-like PLs, for which the aforementioned bending potential was replaced by a harmonic potential U normalr normalo normald ( θ ) = 1 2 k h ( θ θ 0 ) 2 where k h = 100 kJ mol –1 rad –2 is a force constant and θ 0 is an equilibrium bond angle, which is fixed according to the geometry of each PL molecule (see Figure ). This model has been used in previous studies of polymer composites. ,, All simulations in this work were performed using the GROMACS 5.0 MD simulation package…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations